The Effects of the Barbell Hip Thrust on Post-Activation Performance Enhancement of Change of Direction Speed in College-Aged Men and Women - Ashley J. Orjalo; Samuel J. Callaghan; Robert G. Lockie (MDPI AG, 2020)
This study investigated whether the barbell hip thrust (BHT) enhanced change-of-direction (COD) speed measured by the 505 COD speed test. Forty recreationally trained individuals completed three sessions. Session 1 included one-repetition maximum (1RM) BHT testing to measure absolute and relative strength. Sessions 2 and 3 involved two counter-balanced conditioning activities (CAs): 3 sets × 5 repetitions of the BHT at 85% 1RM and a control condition (CC; 6 min rest). The 505 COD speed test was performed 5 and 2.5 min pre-CA, and 4, 8, 12, and 16 min post-CA in each session. A 2 × 5 repeated-measures ANOVA (p < 0.05) calculated performance changes across time post-CA. A 2 × 2 repeated-measures ANOVA analyzed best potentiated performance. Partial correlations controlling for sex calculated relationships between the 1RM BHT and 505 COD speed test percent potentiation. There was a significant main effect for time (p < 0.001), but not for condition (p = 0.271) or condition × time (p = 0.295). There were no significant correlations between 1RM BHT and potentiation. The 85% 1RM BHT did potentiate the 505 4-16 min post-CA but no more than the CC. Nonetheless, a heavy BHT could be programmed prior to COD drills as COD speed could be potentiated and performance improved in men and women.